Constructing Percentiles Norms for Male Students Participating in the Physical Fitness Preparation Course - Mohammed Bakir (My University, 2011)
The purpose of the current study was to evaluate the physical fitness components levels for the male students were participated in the physical fitness preparation course at the faculty of physical education at the University of Jordan during the study years (2006-2007) (2007-2008) 2008-2009). Descriptive approach was used as statistical treatment. Ninety male students were selected randomly for the study, seven fitness tests were selected (respiratory endurance, muscle endurance (sit-up and push-up), explosive -power, speed, flexibility and agility). Means, standard deviation, skew ness and percentile ranks were used. The researcher recommended to utilize the norms obtained to construct percentile norms to assess the physical fitness ability objectively in the practical part of the physical fitness course.

هدفت هذه الدراسة للتعرف الى مستوى القدرات البدنية، وبناء مستويات معيارية لبعض عناصر اللياقة البدنية للطلبة الذكور والمسجلين في مادة الأعداد البدني في كلية التربية الرياضية في الجامعة الأردنية في الأعوام (2006-2007)، (2007-2008)، (2008-2009)، وقد أستخدم الباحث المنهج الوصفي لملائمته لطبيعة الدراسة، وقد تكونت عينة الدراسة من 90 طالباً من طلاب كلية التربية الرياضية والمسجلين في مادة الإعداد البدني، حيث تم اختيارهم بالطريقة العشوائية، وتم اختيار سبعة اختبارات بدنية ممثلة في التحمل الدوري التنفسي، التحمل العضلي ممثل في (الجلوس من الرقود والضغط على اليدين) القوة الانفجارية، السرعة، المرونة والرشاقة، وقد تم استخدام المتوسطات الحسابية و الانحرافات المعيارية، الحد الأدنى والحد الأعلى، معامل الالتواء والدرجات المئينية في المعالجة الإحصائية. وقد توصلت نتائج الدراسة الى بناء مستويات معيارية لعناصر اللياقة البدنية للطلبة الذكور في مادة الإعداد البدني، وأوصى الباحث باستخدام هذه المعايير لتقييم القدرات البدنية للطلاب تقييماُ موضوعياً في الجزء العملي لمادة الإعداد البدني.
بناء مستويات معيارية لبعض عناصر اللياقة البدنية لطلبة مساق الإعداد البدني